Toward High Fidelity Materials Property Prediction from Multiscale Modeling and Simulation. Issue 1 (4th October 2019) - Vassaux, Maxime; Sinclair, Robert C.; Richardson, Robin A.; Suter, James L.; Coveney, Peter V.
Abstract: The current approach to materials discovery and design remains dominated by experimental testing, frequently based on little more than trial and error. With the advent of ever more powerful computers, rapid, reliable, and reproducible computer simulations are beginning to represent a feasible alternative. As high performance computing reaches the exascale, exploiting the resources efficiently presents interesting challenges and opportunities. Multiscale modeling and simulation of materials are extremely promising candidates for exploiting these resources based on the assumption of a separation of scales in the architectures of nanomaterials. Examples of hierarchical and concurrent multiscale approaches are presented which benefit from the weak scaling of monolithic applications, thereby efficiently exploiting large scale computational resources. Several multiscale techniques, incorporating the electronic to the continuum scale, which can be applied to the efficient design of a range of nanocomposites, are discussed. Then the work on the development of a software toolkit designed to provide verification, validation, and uncertainty quantification to support actionable prediction from such calculations is discussed. Abstract : Materials discovery and design remain dominated by experimental testing . With the advent of powerful exascale computers, rapid, reliable, and reproducible computer simulations are beginning to represent a feasible alternative. Exploiting these resources for materials design poses a new set of challenges and opportunities which we discuss using specific applications in this progress report.